The new Malay heartland: the pursuit of dream and hope along the pace of globalization - Abdullah, Azli; Wahid, Julaihi; Shukri, Sharyzee; Mohamad Jamil, Mohd Azli; Aziz, Adrianta (Universiti Sains Malaysia, 2022)
Malaysia is a rapidly developing country that has only taken 30 years to transition from a predominantly agricultural economy to a manufacturing-dependent society. Villager migration to the city has resulted in a new generation of urban communities that have separated themselves from traditional subsistence farming but maintain sporadic contact with their hometowns. The lives and livelihoods of these urban immigrants in the city have improved due to new jobs, environments, and lifestyles, but some have failed. The Malay settlements became increasingly vulnerable after the migration to the city in terms of both identity and cultural density. Environmental changes in Malay settlements following migration are rarely discussed. Even though the link between migration and the destruction of Malay settlements was very strong, the discussion only raised concerns about the city. The phenomenon and dreams of Malays migrating to the city are the focus of this research. Some Malays were successful after leaving their settlement areas, while others failed and returned to their settlement areas. To generate discussions, mixed-methods were used, including case studies, questionnaires with residents, observations, group interviews and triangulation technique. Although Malay settlements are increasingly being destroyed, the study discovered that individual motivational factors are the primary source of attraction for Malays to the city.